2022
DOI: 10.1186/s12913-022-08591-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of prescribing decisions for off-patent biological medicines in Belgium: a qualitative study

Abstract: Background A competitive market for off-patent biologicals leads to more affordable and high-quality healthcare. In recent years, Belgium has been characterized by its low use of biosimilars and by its shifts from off-patent biologicals toward new alternative therapies. Yet, the prescribing decisions involved in these observations are poorly understood. This study aims to better understand prescribing choices among Belgian physicians in the ambulatory care setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…This strategy is used to influence the physicians' prescribing behavior. The strategies used by various pharmaceutical companies around the world such as Jordania 12 , the United States 13 , Ethiopia 14 , Lebanon 15 , India 16,17 , Australia 18 , and Belgium 19 . Mix marketing strategy is the most strategy used by pharmaceutical companies.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy is used to influence the physicians' prescribing behavior. The strategies used by various pharmaceutical companies around the world such as Jordania 12 , the United States 13 , Ethiopia 14 , Lebanon 15 , India 16,17 , Australia 18 , and Belgium 19 . Mix marketing strategy is the most strategy used by pharmaceutical companies.…”
Section: Resultsmentioning
confidence: 99%
“…In this line, our analysis indicated that shifts in drugs utilization towards on-patent immunomodulators occurred after loss of exclusivities for TNF-alfa inhibitors, notwithstanding higher acquisition costs. As indicated by Vandenplas et al, there can be multiple determinants of prescribing decisions (Vandenplas et al, 2022). Shifts in prescribing from off-patent TNF-alfa inhibitors towards higher-cost second and third generation on-patent products could be partly due to the greater availability of dedicated physician education and patient support programs for these products.…”
Section: Discussionmentioning
confidence: 99%
“…For new products, physicians require substantial information about the efficacy and safety profile of the drug, various clinical trials done for the molecule, the approvals given by the relevant authorities and additional benefits as compared to established brands (Mizik and Jacobson, 2004;Narayanan and Manchanda, 2009;Faisal et al, 2020;Morgan and Zane, 2022). Since PSRs are the ones who introduce new products to physicians, the onus of explaining newly launched products and providing required information for reducing uncertainty about newly launched drugs lies with PSR (Narayanan and Manchanda, 2009;Alkhateeb et al, 2011;Faisal et al, 2020;Vandenplas et al, 2022). Avorn et al, 1982 have observed that scientific information is a major source of influence on physician's prescription behaviour, more so for new drugs (McGettigan et al, 2001;Narayanan and Manchanda, 2009;Faisal et al, 2020) as compared to established brands.…”
Section: Informative Detailing For New Brandsmentioning
confidence: 99%
“…Pharmaceutical companies, while meeting the health needs of the consumers, also strive to generate profits for research, development and sustenance (Ion et al , 2021). Hence, pharmaceutical companies play a crucial role in enabling physicians to make informed choices (Levy, 1994; Menebo, 2021; Vandenplas et al , 2022) and cater to patient needs effectively.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation